PREVALENCE OF INTESTINAL HELMINTHIASIS IN CHILDREN AT NORTH KEPUTRAN SURABAYA AT 2017 - Prasetyo, Hana Naili; Prasetyo, Heru (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Parasite infection is still an endemic disease that can be found in any place in Indonesia that can cause problems in public health, especially for children. Intestinal helminthiasis can interfere with children's growth and development which will affect their quality of life. Purpose: The purpose of this research is to find out the prevalence of intestinal helminthiasis among children in Pasar Kampung Keputran Surabaya. It is located at the riverbank and the majority people are immigrants that lead to population density and slum. Method: This descriptive observational study anal swab specimens with Scotch adhesive tape swab method and fecal specimen were examined microscopically at the Laboratory of Parasitology, Faculty of Medicine, Airlangga University. Result: according to the finding of the anal swab and stool examination: 36 % specimens were infected by intestinal helminth as follows: Enterobiasis 28 %, Ascariasis 4% and Hymenolepiasis 4% Intestinal parasite sufferers 62,5% male and 37,5% women with vulnerable age of a patient 6-11 year. Conclusion: It can be concluded that the prevalence of intestinal helminthiasis in children in the village of Pasar Keputran Utara Surabaya is quite high, ie 36% infected intestinal worms. Gender and age are also influential. Proven male patients are higher than women. Densely populated areas, poor environmental and sanitation, and the intensity and intensity of child contact with the outdoors are responsible for high rates of intestinal parasite infection in the area.